Effect of temperature on tribological properties of palm biodiesel - Haseeb, A.S. Md. Abdul; Sia, S.Y.; Fazal, M.A.; Masjuki, Haji Hassan (2010)
Biodiesel, as an alternative fuel is steadily gaining attention to replace petroleum diesel partially or completely. The tribological performance of biodiesel is crucial for its application in automobiles. In the present study, effect of temperature on the tribological performance of palm biodiesel was investigated by using four ball wear machine. Tests were conducted at temperatures 30, 45, 60 and 75 degrees C, under a normal load of 40 kg for 1 h at speed 1200 rpm. For each temperature, the tribological properties of petroleum diesel (BO) and three biodiesel blends like B10, B20, B50 were investigated and compared. During the wear test, frictional torque was recorded on line. Wear scars in tested ball were investigated by optical microscopy. Results show that friction and wear increase with increasing temperature. (C) 2009 Elsevier Ltd. All rights reserved.